Preparation method of PTFE (Polytetrafluoroethylene) for dry-method electrode adhesive

By improving the preparation method of PTFE, it improves its application performance in the dry electrode adhesive, and solves the problem that PVDF cannot fibrosis and use toxic solvents in existing technologies, and realizes higher stretch strength and conductive performance. Reduce production costs and environmental pollution.

CN119331566APending Publication Date: 2025-01-21ZHEJIANG JUSHENG FLUOROCHEM

Patent Information

Application Number
CN202411547041.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing dry electrode adhesive material PVDF cannot be fibrated, which limits its application and requires the use of toxic and volatile solvents during processing, resulting in environmental pollution and health risks.

Method used

The improved PTFE preparation method is adopted to improve the stretch strength and conductivity of PTFE through the emulsion aggregation reaction and passivation modification steps, so that it is suitable for the dry electrode adhesive.

Benefits of technology

The modified PTFE's application performance in the dry electrode adhesive has significantly improved, has higher stretching strength and conductive performance, and meets the needs of the dry method electrode. pollute.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331566A_ABST
    Figure CN119331566A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of PTFE for a dry-method electrode adhesive, and relates to the technical field of battery materials. The method comprises the following specific steps: adding deionized water into a reaction kettle, and heating a jacket of the reaction kettle; adding an initiator, a surfactant and a chain transfer agent, and uniformly stirring; adding a tetrafluoroethylene monomer, carrying out emulsion polymerization reaction, and controlling the reaction temperature and pressure; after the reaction is finished, cooling and filtering to obtain PTFE emulsion, and drying the PTFE emulsion to obtain PTFE powder; and coating conductive carbon powder on the surface of the PTFE powder for passivation modification to obtain the PTFE for the dry-method electrode adhesive. The dry-method electrode has higher tensile strength and conductivity, and can better meet the requirements of the dry-method electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, in particular to a method for preparing PTFE for dry electrode adhesive. Background Art

[0002] At present, dry electrode preparation technology is widely used in lithium-ion batteries and other fields. Lithium-ion batteries have become the main power source for portable electronic devices, electric vehicles and energy storage systems due to their advantages such as high energy density, long cycle life and low self-discharge rate. However, there are many problems with the traditional wet electrode preparation process. The wet process requires the active material, conductive agent and adhesive to be mixed in a solvent to prepare a slurry, and then the slurry is evenly coated on the current collector by a coater, followed by drying and roll forming. The process is complicated and requires multiple steps, including coating, drying, solvent recovery, etc. The production cost is high, and there are environmental pollution problems in the use and recovery of solvents.

[0003] Public patent information: US62 / 650903 provides a dry electrode membrane and an energy storage device including the dry electrode membrane, which includes a microparticle non-fibrillated binder with a certain particle size. The electrode membrane exhibits improved mechanical and processing properties. Also provided is a method for processing such a microparticle non-fibrillated electrode membrane binder and incorporating the microparticle non-fibrillated binder into the electrode membrane.

[0004] In the prior art, the widely used adhesive is mainly polyvinylidene fluoride (PVDF), which has the advantages of good chemical stability and excellent electrochemical performance. However, the main disadvantage of PVDF is that it cannot be fiberized and can only be used in electrostatic spraying, which limits its application in dry electrodes. In addition, PVDF requires the use of organic solvents such as N-methylpyrrolidone (NMP) during processing. These solvents are toxic and volatile, and have adverse effects on the environment and the health of operators. Therefore, it is particularly important to find an adhesive that can replace PVDF and is suitable for the preparation of dry electrodes.

[0005] In contrast, polytetrafluoroethylene (PTFE) has the advantages of large molecular weight, the ability to form long fibers, strong chemical inertness and corrosion resistance. As an adhesive material, PTFE can significantly simplify the electrode preparation process, eliminate the use of solvents, and reduce environmental pollution and production costs. In addition, PTFE has excellent mechanical properties and high temperature resistance, which allows it to remain stable under extreme working conditions. Therefore, PTFE has become an ideal dry electrode adhesive material. However, there are still some problems with the existing PTFE production process and product performance, such as low tensile strength, insufficient conductivity, and poor adhesion after mixing with other non-fibrillated materials. These problems need to be solved by improving the production process and material modification to meet the needs of dry electrode preparation.

[0006] Based on this, the present invention aims to provide an improved PTFE preparation method, which improves its application performance in dry electrode adhesives by optimizing the polymerization process and modifying PTFE, thereby overcoming the shortcomings of the prior art. Summary of the invention

[0007] The present invention provides a method for preparing PTFE for dry electrode adhesive. By improving the preparation method of PTFE, its application performance in dry electrode adhesive is significantly improved. The modified PTFE has higher tensile strength and electrical conductivity, and can meet the needs of dry electrodes.

[0008] In order to achieve the above-mentioned invention object, this method proposes the following solution: A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1000-1200 parts by mass of deionized water into the reactor, and heat the reactor jacket; (2) Add 0.3-0.6 parts of initiator, 1-4 parts of surfactant and 0.5-3 parts of chain transfer agent and stir evenly; (3) Add 80-120 parts of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

[0009] In one embodiment, the initiator is selected from at least one of potassium persulfate, sodium persulfate, hydrogen peroxide or azobisisobutyronitrile.

[0010] In one embodiment, the surfactant is selected from at least one of potassium perfluorooctanoate, ammonium perfluorooctanoate, potassium perfluorodecanoate or sodium dodecyl sulfate.

[0011] In one embodiment, the chain transfer agent is selected from isopropanol, methanol, ethanol or butadiene.

[0012] In one embodiment, the reaction temperature is 50-70° C. and the pressure is 0.3-0.6 MPa.

[0013] In one embodiment, the particle size of the PTFE powder is 0.1-10 microns.

[0014] In one embodiment, the passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor in the following proportions: 3-6 parts by weight of ethyl isocyanate acrylate, 10-15 parts by weight of hydroxylated multi-walled carbon nanotubes, 1-4 parts by weight of stannous octoate, and 1000-1300 parts by weight of toluene. Heat the mixture to 60-70°C and stir for 30-100 minutes. K3: Add 100-170 parts by weight of mercapto-modified PTFE polymer powder, 0.003-0.02 parts by weight of methyl tributyltin maleate, and 0.5-3.2 parts of photoinitiator, introduce nitrogen, and place the reaction system under an ultraviolet lamp for click reaction under stirring for 30-70 minutes, filter, dry, and grind by ball mill for 10-30 minutes to obtain a surface-passivated PTFE polymer.

[0015] In one embodiment, the plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz RF; the power range is 50 to 100 watts; the operating pressure is 50 to 100 mTorr; the treatment time is 10 to 40 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 15-30 ml / min.

[0016] In one embodiment, the photoinitiator in step K3 is selected from at least one of 2,2-dimethoxy-2-phenylethanone, 2-methyl-4'-methylmercapto-2-morpholinopropiophenone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0017] Technical mechanism: The isocyanate ethyl acrylate and the hydroxylated multi-walled carbon nanotube undergo a condensation reaction to obtain the multi-walled carbon nanotube containing ethyl acrylate; In terms of reaction mechanism, the condensation reaction of isocyanate ethyl acrylate and hydroxylated multi-walled carbon nanotubes is connected through the chemical reaction between the isocyanate group and the hydroxyl group to form multi-walled carbon nanotubes containing ethyl acrylate functional groups. The mercapto-modified PTFE polymer and methyl tributyltin maleate form a stable thioether bond through the mercapto-ene Michael addition reaction, and then the same Michael addition reaction occurs with the multi-walled carbon nanotubes containing ethyl acrylate, and the grafting is completed under ultraviolet light irradiation. The grinding process makes the nanotubes evenly coated on the surface of the PTFE polymer particles to form a surface-passivated PTFE polymer.

[0018] Technical effect: 1. Tributyltin helps improve the electrochemical performance and cycle stability of lithium battery binders by providing additional functional groups and enhancing interface stability. The beneficial effects of polyurethane functional groups such as isocyanate and carbamate on lithium battery binders are mainly reflected in improving the cohesion and adhesion of the binder, enhancing the structural integrity of the battery electrode, and thus improving the cycle life and stability of the battery.

[0019] 2. The present invention significantly improves the application performance of PTFE in dry electrode adhesive by improving the preparation method of PTFE. The modified PTFE has higher tensile strength and conductivity, which can meet the needs of dry electrodes. At the same time, the present invention simplifies the electrode preparation process, reduces production costs, and has significant economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The DSC graph of PTFE prepared in Example 1; Figure 2 The particle size scanning electron microscope of the PTFE emulsion prepared in Example 1; Figure 3 This is the particle size distribution diagram of the PTFE emulsion prepared in Example 1. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0022] Example 1 A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1000 g of deionized water into the reactor and heat the reactor jacket; (2) Add 0.3g initiator, 1g surfactant and 0.5g chain transfer agent and stir evenly; (3) Add 80 g of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

[0023] The initiator is selected from potassium persulfate.

[0024] The surfactant is selected from potassium perfluorooctanoate.

[0025] The chain transfer agent is selected from isopropyl alcohol.

[0026] The reaction temperature is 50°C and the pressure is 0.3 MPa.

[0027] The passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor: 3 g of ethyl isocyanate acrylate, 10 g of hydroxylated multi-walled carbon nanotubes, 1 g of stannous octoate, and 1000 g of toluene. Heat the mixture to 60°C and stir for 30 minutes. K3: Add 100 g of mercapto-modified PTFE polymer powder, 0.003 g of methyl tributyltin maleate, and 0.5 g of photoinitiator, introduce nitrogen, and place the reaction system under a UV lamp for a click reaction while stirring. React for 30 minutes, filter, dry, and grind with a ball mill for 10 minutes to obtain a surface-passivated PTFE polymer.

[0028] The plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz radio frequency; the power range is 50 watts; the operating pressure is 50 mTorr; the treatment time is 10 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 15 ml / min.

[0029] The photoinitiator in step K3 is selected from 2,2-dimethoxy-2-phenylethanone.

[0030] Example 2 A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1100 g of deionized water into the reactor and heat the reactor jacket; (2) Add 0.4g initiator, 2g surfactant and 1.5g chain transfer agent and stir evenly; (3) Add 100 g of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

[0031] The initiator is selected from sodium persulfate.

[0032] The surfactant is selected from ammonium perfluorooctanoate.

[0033] The chain transfer agent is selected from methanol.

[0034] The reaction temperature is 60°C and the pressure is 0.4 MPa.

[0035] The passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor: 4 g ethyl isocyanate acrylate, 12 g hydroxylated multi-walled carbon nanotubes, 2 g stannous octoate, 1100 g toluene, heat the mixture to 65°C and stir for 50 minutes. K3: Add 120 g of mercapto-modified PTFE polymer powder, 0.008 g of methyl tributyltin maleate, and 1.2 g of photoinitiator, introduce nitrogen, and place the reaction system under a UV lamp for a click reaction while stirring. React for 45 minutes, filter, dry, and grind with a ball mill for 20 minutes to obtain a surface-passivated PTFE polymer.

[0036] The plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz radio frequency; the power range is 75 watts; the operating pressure is 75 mTorr; the treatment time is 20 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 20 ml / min.

[0037] The photoinitiator in step K3 is selected from 2,2-dimethoxy-2-phenylethanone.

[0038] Example 3 A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1100 g of deionized water into the reactor and heat the reactor jacket; (2) Add 0.5g initiator, 3g surfactant and 2.5g chain transfer agent and stir evenly; (3) Add 100 g of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

[0039] The initiator is selected from hydrogen peroxide.

[0040] The surfactant is selected from potassium perfluorodecanoate.

[0041] The chain transfer agent is selected from methanol.

[0042] The reaction temperature is 60°C and the pressure is 0.5 MPa.

[0043] The passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor: 5 g ethyl isocyanate acrylate, 13.5 g hydroxylated multi-walled carbon nanotubes, 3 g stannous octoate, 1200 g toluene, heat the mixture to 65°C and stir for 80 minutes. K3: Add 150 g of mercapto-modified PTFE polymer powder, 0.01 g of methyl tributyltin maleate, and 2.8 g of photoinitiator, introduce nitrogen, and place the reaction system under a UV lamp for a click reaction while stirring. React for 50 minutes, filter, dry, and grind with a ball mill for 20 minutes to obtain a surface-passivated PTFE polymer.

[0044] The plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz radio frequency; the power range is 75 watts; the operating pressure is 75 mTorr; the treatment time is 30 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 25 ml / min.

[0045] The photoinitiator in step K3 is selected from 2-methyl-4'-methylmercapto-2-morpholinopropiophenone.

[0046] Example 4 A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1200 g of deionized water into the reactor and heat the reactor jacket; (2) Add 0.6g initiator, 4g surfactant and 3g chain transfer agent and stir evenly; (3) Add 120 g of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

[0047] The initiator is selected from perazobisisobutyronitrile.

[0048] The surfactant is selected from sodium lauryl sulfate.

[0049] The chain transfer agent is selected from butadiene.

[0050] The reaction temperature is 70° C. and the pressure is 0.6 MPa.

[0051] The passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor: 6 g ethyl isocyanate acrylate, 15 g hydroxylated multi-walled carbon nanotubes, 4 g stannous octoate, 1300 g toluene, heat the mixture to 70°C and stir for 100 minutes. K3: Add 170 g of mercapto-modified PTFE polymer powder, 0.02 g of methyl tributyltin maleate, and 3.2 g of photoinitiator, introduce nitrogen, and place the reaction system under a UV lamp for a click reaction while stirring. The reaction lasts for 70 minutes, and the mixture is filtered, dried, and ball-milled for 30 minutes to obtain a surface-passivated PTFE polymer.

[0052] The plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz radio frequency; the power range is 100 watts; the operating pressure is 100 mTorr; the treatment time is 40 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 30 ml / min.

[0053] The photoinitiator in step K3 is selected from 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0054] Comparative Example 1 This example is used as a comparative example of Example 1, and is consistent with Example 1, except that the PTFE is not passivated and modified.

[0055] Comparative Example 2 This example is used as a comparative example of Example 1, and is consistent with Example 1, except that isocyanate ethyl acrylate is not added when the PTFE is passivated and modified.

[0056] Comparative Example 3 This example is used as a comparative example of Example 1, and is consistent with Example 1, except that methyl tributyltin maleate is not added when the PTFE is passivated and modified.

[0057] Evaluation of Examples 1. Tensile strength: Cut the prepared dry electrode into samples with a size of 100mm × 10mm. Prepare at least five samples for each material. Use an electronic universal testing machine for testing.

[0058] 2. Conductivity test: Cut the prepared dry electrode into samples with a size of 10mm × 10mm. Prepare at least five samples for each material. Use a four-probe tester for testing.

[0059] Test results: Tensile strength MPa Conductivity S / cm Example 1 37 8.6 Example 2 41 9.1 Example 3 40 9.7 Example 4 42 10.5 Comparative Example 1 33 3.4 Comparative Example 2 35 5.8 Comparative Example 3 34 6.2 It can be seen from the above test results that the application performance of the modified PTFE provided by the present invention in dry-process electrodes is significantly improved, it has higher tensile strength and conductivity, and can better meet the needs of dry-process electrodes.

[0060] The above are only specific embodiments of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. A method for preparing PTFE for a dry electrode adhesive, the operating steps of which are: (1) Add 1000-1200 parts by mass of deionized water into the reactor, and heat the reactor jacket; (2) Add 0.3-0.6 parts of initiator, 1-4 parts of surfactant and 0.5-3 parts of chain transfer agent and stir evenly; (3) Add 80-120 parts of tetrafluoroethylene monomer to carry out emulsion polymerization reaction, and control the reaction temperature and pressure; (4) After the reaction is completed, the temperature is lowered and filtered to obtain a PTFE emulsion, and the PTFE emulsion is dried to obtain a PTFE powder; (5) The surface of PTFE powder is coated with conductive carbon powder for passivation modification to obtain PTFE for dry electrode adhesive.

2. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The initiator is selected from at least one of potassium persulfate, sodium persulfate, hydrogen peroxide or azobisisobutyronitrile.

3. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The surfactant is selected from at least one of potassium perfluorooctanoate, ammonium perfluorooctanoate, potassium perfluorodecanoate or sodium dodecyl sulfate.

4. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The chain transfer agent is selected from isopropanol, methanol, ethanol or butadiene.

5. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The reaction temperature is 50-70°C and the pressure is 0.3-0.6 MPa.

6. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The particle size of the PTFE powder is 0.1-10 microns.

7. The method for preparing PTFE for a dry electrode adhesive according to claim 1, characterized in that: The passivation modification step is: K1: Plasma surface treatment of PTFE polymer powder is performed under low pressure to obtain mercapto-modified PTFE polymer powder; K2: Add the following chemical substances to the stirred reactor in the following proportions: 3-6 parts by weight of ethyl isocyanate acrylate, 10-15 parts by weight of hydroxylated multi-walled carbon nanotubes, 1-4 parts by weight of stannous octoate, and 1000-1300 parts by weight of toluene. Heat the mixture to 60-70°C and stir for 30-100 minutes. K3: Add 100-170 parts by weight of mercapto-modified PTFE polymer powder, 0.003-0.02 parts by weight of methyl tributyltin maleate, and 0.5-3.2 parts of photoinitiator, introduce nitrogen, and place the reaction system under an ultraviolet lamp for click reaction under stirring for 30-70 minutes, filter, dry, and grind by ball mill for 10-30 minutes to obtain a surface-passivated PTFE polymer.

8. The method for preparing PTFE for a dry electrode adhesive according to claim 7, characterized in that: The plasma treatment parameters of step K1 are: the power frequency is set to 13.56 MHz radio frequency; the power range is 50 to 100 watts; the operating pressure is 50 to 100 mTorr; the treatment time is 10 to 40 minutes; and thioglycolic acid vapor is used as the plasma gas with a flow rate of 15-30 ml / min.

9. The method for preparing PTFE for a dry electrode adhesive according to claim 7, characterized in that: The photoinitiator in step K3 is selected from at least one of 2,2-dimethoxy-2-phenylethanone, 2-methyl-4'-methylmercapto-2-morpholinopropiophenone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

Citation Information

Patent Citations

  • Compositions and methods for dry electrode films including microparticulate non-fibrillizable binders

    US62650903P0

Cited By

  • Conductive carbon coated modified PTFE / disulfide bond composite binder, positive plate and preparation method

    CN120737762A